2021
DOI: 10.20471/acc.2021.60.03.12
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-MIBI SPECT/CT Scintigraphy and Ultrasound of the Anterior Neck Region in Diagnosing Parathyroid Gland Pathology in Patients with Thyroid Nodules

Abstract: Parathyroid scintigraphy with 99m Tc-MIBI is an imaging technique used in nuclear medicine and performed in patients with suspected hyperparathyroidism (HPT). The objective of this study was to evaluate the role of this technique in patients who, along with suspected HPT, also have thyroid nodules. Retrospective analysis included a period of 8 years (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). The study included 91 patients with clinical or laboratory suspected HPT. Pathologic changes in parathyroid gland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This situation was explained by the fact that cellular atypia developing due to HT suggested AUS-FLUS diagnosis for non-malignant nodules and negatively affected diagnostic value of FNAB 2 . It is possible to come across literature articles indicating that a group of diseases including HT may increase false positivity even in noninvasive diagnostic tools such as scintigraphy scan with technetium-99m (sestamibi) 29 . In the article by Ho et al, the rate of malignancy has been reported as 38.6% (135/350) even in patients who were urgently operated on because they were diagnosed with AUS-FLUS and had suspicious features 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This situation was explained by the fact that cellular atypia developing due to HT suggested AUS-FLUS diagnosis for non-malignant nodules and negatively affected diagnostic value of FNAB 2 . It is possible to come across literature articles indicating that a group of diseases including HT may increase false positivity even in noninvasive diagnostic tools such as scintigraphy scan with technetium-99m (sestamibi) 29 . In the article by Ho et al, the rate of malignancy has been reported as 38.6% (135/350) even in patients who were urgently operated on because they were diagnosed with AUS-FLUS and had suspicious features 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, DECT has a higher thyroid radioiodine exposure than US and MIBI. Overall, more studies are needed to explore the factors that may impact the localization accuracy of DECT, such as the fact that DECT localization failed in 3 (3/19) patients in our study who also had thyroid cancer [30].…”
Section: Diagnostic E Ciency Us 99m Tc-mibi Spect/ct Andmentioning
confidence: 99%